Outcome of Intra-Articular Steroid Injection in Osteoarthritis of Knee: A One Year Experience (Journal of Chittagong Medical College Teachers' Association, 2010)
Keywords: osteoarthritis of knee; intra-articular steroid; outcomeDOI: 10.3329/jcmcta.v20i2.5624Journal of Chittagong Medical College Teachers' Association 2009: 20(2):33-38